2017
DOI: 10.1097/tp.0000000000001648
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Trials for Immunosuppression in Transplantation

Abstract: Currently trials of immunosuppression in transplantation are in decline because their objectives remain focused on improving acute rejection rates and graft survival in the first 12 months. With 1 year renal graft survival rates of greater than 90% the best that can be hoped for is noninferiority trial outcomes compared with current standard of care. Current trial design is not leading to novel therapies improving long-term outcomes and safety, and hence important unmet clinical needs in transplantation remain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
56
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(58 citation statements)
references
References 61 publications
0
56
0
2
Order By: Relevance
“…Despite chronic antibody mediated rejection (ABMR) constituting one of the main reasons for late graft failure, [1][2][3] there are no approved drugs for its prevention or treatment. 4 Chronic ABMR is characterized by a silent clinical evolution that can delay its diagnosis. 5,6 Criteria to define chronic ABMR have been modified since its description in 2005.…”
Section: Introductionmentioning
confidence: 99%
“…Despite chronic antibody mediated rejection (ABMR) constituting one of the main reasons for late graft failure, [1][2][3] there are no approved drugs for its prevention or treatment. 4 Chronic ABMR is characterized by a silent clinical evolution that can delay its diagnosis. 5,6 Criteria to define chronic ABMR have been modified since its description in 2005.…”
Section: Introductionmentioning
confidence: 99%
“…3 A review of this problem, sponsored by the Transplantation Society, has suggested that clinical trials should focus on outcomes such as subclinical rejection. 2 The merits or otherwise of using surrogate outcomes has been debated recently in CJS. 4,5 It is difficult to imagine that this solution will inspire sufficient enthusiasm to break the logjam.…”
Section: Editorial • éDitorialmentioning
confidence: 99%
“…For example, we have used the same immunosuppressants against rejection after transplantation for a quarter of a century and face the prospect of being unable to develop new therapies because 1-year survival rates of 95% leave little room for improvement. 2 Cancer chemotherapy research appears to be trapped in the doldrums where clinical trials of endless recombinations of similar agents prevail. Or consider minimally invasive surgery, where great technological efforts are made to reduce the number of port sites, which, in effect, spares the patient a couple of rapidly healing 5 mm stab wounds.…”
Section: Editorial • éDitorialmentioning
confidence: 99%
“…Prenons l'exemple des médi-caments immunosuppresseurs contre le rejet d'une greffe. Nous utilizons les mêmes molécules depuis un quart de siècle: avec des taux de survie d'un an après la greffe de 95 % -difficile de faire mieux -, avons-nous encore la possibilité de développer de nouvelles thérapies 2 ? Et que dire de la recherche en chimiothérapie anticancéreuse, enlisée, selon toute apparence, dans une situation où prévalent les essais cliniques qui testent des recombinaisons infinies d'agents similaires?…”
unclassified
“…Bien que ces résultats aient été confirmés il y a 25 ans dans le cadre de 2 grands essais d'homologation, 18 nouveaux essais cliniques alé-atoires ont depuis été entrepris avec exactement les mêmes résul-tats 3 . Un examen de ce problème, parrainé par la Transplantation Society, propose que les essais cliniques devraient se concentrer sur des résultats comme le rejet subclinique 2 . Le bien-fondé -s'il y a lieu -du recours à des critères de substitution a été abordé récem-ment dans le JCC 4,5 .…”
unclassified